RANCANG BANGUN MARKETPLACE BAGI UMKM DESA LANGSE KEC. MARGOREJO - Ade Indra Prasetya Pradana; Listiarini Edy Sudiati; Nịnik Haryani (LPPM Politeknik Saint Paul Sorong, 2023)
One of the superior products of Langse village, Margorejo sub-district is tempe chips, with a total of 15 business actors, and most of them become home industry centers that absorb the energy of the majority of the Langse village community. In addition, there are other micro, small and medium enterprises, namely batik and vegetable and fruit traders. However, with the Covid 19 pandemic, the MSMEs of Langse village were greatly affected, due to the declining purchasing power of the people, the marketing system still uses the traditional system by trading directly in the market or entrusting merchandise to stalls and limited marketing reach. The purpose of this research is to develop MSMEs in Langke village, Margorejo sub-district, which had slumped by building a network between MSME actors and expanding marketing reach by building a marketplace.